Three Tales of Scientific Success. Issue 5 (December 2016) - Massimi, Michela
Abstract : Success-to-truth inferences have been the realist stronghold for a long time. Scientific success is the parameter by which realists claim to discern approximately true theories from false ones. But scientific success needs to be probed a bit deeper. In this article, I tell three tales of scientific success, by considering in turn success from nowhere, success from here now, and success from within. I argue for a suitable version of success from within that can do justice to the historically situated nature of our scientific knowledge. The outcome is a new way of thinking about success-to-truth inferences along perspectivalist lines.